RARE SULFOSALTS FROM VULCANO, AEOLIAN ISLANDS, ITALY. VII. CL-BEARING GALENOBISMUTITE - Pinto D.; Garavelli A.; Vurro F.; Balić-Žunić T.; Makovicky E.; Bonaccorsi E.; Borodaev Y.S.; Garbarino C.; Mozgova N.N. (My University, 2006)
Cl-bearing galenobismutite (with Cl ranging from 0.12 to 1.45 wt.%), discovered among high-temperature fumarole incrustations at "La Fossa" crater, Island of Vulcano, Italy, has been chemically and structurally investigated. The mineral is commonly associated with bismuthinite, cannizzarite, lillianite, heyrovskýite and galena, and rarely with kirkiite, vurroite and other less well characterized Pb(Bi)-sulfochlorides. Electron-microprobe investigations show that Cl-bearing galenobismutite from Volcano has a wide compositional field (Pb:Bi atomic ratio ranging from 0.52 to 0.72). The statistical analysis of chemical data shows correlations between the main elements and chlorine, positive Pb versus Cl and negative Bi versus Cl, according to the coupled heterovalent substitution scheme: Pb2+ + Cl- ⇌ Bi3+ + S2-. The compositional variation of Cl-bearing galenobismutite can be represented by the general empirical formula Pb1+xBi2-x (S4-x-yClxSey), with 0 < x < 0.3 and 0 < y < 0.2, indicating the extent of departure from the ideal composition PbBi2S4 toward an increase of the Pb content and a decrease of Bi. The phase IV, synthetic analogue of galenobismutite in the system Pb-Bi-S, has the compositional field extending from ideal composition toward decreasing Pb (Pb:Bi atomic ratio in the range 0.50-0.39). It reflects another type of substitution: 3Pb2+ → 2Bi3+ + □. single-crystal X-ray investigations were performed on two selected crystals of Cl-bearing galenobismutite from Vulcano. The composition of galenobismutite controls the a and b unit-cell parameters, which increase with the increase of the Cl content. The structural refinements converge to R values of 3.10% for 840 reflections [Fo > 4σ(Fo)] and 1.49% for 376 reflections [Fo > 4σ(Fo)], respectively. The structure of Cl-bearing galenobismutite is topologically identical to that of Cl-free galenobismutite. The excess of Pb observed in Cl-bearing galenobismutite is incorporated in the trigonal prismatic M2gb and M3gb sites. No Pb-for-Bi substitution was observed at the octahedral position M1gb. We do not find evidence of a preferential distribution of Cl among the anion positions.
Keywords: CL-BEARING GALENOBISMUTITE; CRYSTAL STRUCTURE; FUMAROLES; ITALY; PB-BI SULFOSALT; VULCANO ISLAND